Perception of Threatening Intention Modulates Brain Processes to Body Actions: Evidence From Event-Related Potentials - Wang, Guan; Wang, Pei; Luo, Junlong; Nan, Wenya (Frontiers in Psychology, 2018)
Efficiently perceiving others’ threating intention conveyed by body actions has great survival value. The current study investigated whether human brain was sensitive to intention difference in body actions by recording event-related potentials (ERPs). For this purpose, a new intention categorization task was developed in which participants sat in front of the computer screen on which the pictures of high threat (HT), moderately threat (MT), and non-threat (NT) body action were presented randomly. Participants were asked to press the corresponding buttons through threatening-level judgement. According to a cluster permutation test, we analyzed N190, N2, EPP and P3. Results showed there was a positive correlation between the amplitude of EPP induced by three kinds of body actions and the reaction time of task. Results also revealed that when the deflection of EPP was less positive, the reaction time was shorter. We suggest that EPP (early posterior positivity) may be an index of body intention processing of brain. Our study reveals that intention perception of body actions modulates brain processing.